Spent fuel alteration model integrating processes of different time-scales. (2020) - Riba, O.; Coene, E.; Silva, O.; Duro, L.
ABSTRACT: A 1D reactive transport model has been implemented in iCP (interface COMSOL Multiphysics and PhreeqC) to assess the corrosion of Spent Fuel (SF), considered as homogeneous UO2 (am, hyd) doped with Pd. The model couples: i) generation of water radiolysis species by alpha and beta radiation considering the complete water radiolysis system with the kinetic reactions involving: H +, OH -, O2, H2 O2, H2, HO2 -, HO2 ·, O·, O -, O2 -, H·, ·OH and e - ii) processes occurring in the spent fuel surface: oxidative dissolution reactions of UO2 (am, hyd) and subsequent reduction of oxidized fuel, considering H2 activation by Pd, and iii) corrosion of Fe(s) in oxic and anoxic conditions. Process i) has been implemented in COMSOL and processes ii) and iii) have been implemented in PHREEQC with their kinetic constants being calibrated with different sets of experimental data published in the open literature. The model yields a UO2 (am, hyd) dissolution rates similar to the values selected in safety assessments.